Attracting East Asian Students to Canadian Graduate Schools - Chen, Liang-Hsuan (Canadian Journal of Higher Education, 2006)
This study seeks to identify factors influencing East Asian international students’ choices of Canadian graduate schools, to assess the strengths and dynamics of the factors influencing enrolment decisions, and to describe possible implications both for the Canadian government and for Canadian universities offering graduate education. The research sample comprised 140 students from China, Hong Kong, Japan, Korea, and Taiwan who enrolled in graduate programs at two large Ontario universities. The research findings reveal the significant influence of academic, economic, environmental, and visa/immigration pulling factors as well as a set of negative pushing factors from third countries such as the United States. Activities related to internationalization of graduate education play a critical role in influencing the choice of a Canadian graduate school. The findings suggest that to attract the “best and brightest” international graduate students, policy makers and institutional administrators should focus on investing in research and ensuring the quality of graduate education while devoting efforts and resources to the internationalization of Canadian graduate education.